Housing Policy in Soviet Russia and Germany between the Two World Wars: Comparative Analysis of Two Systems - Konstantin A. Kholodilin; Mark G. Meerovich (Journal of Urban History, 2018)
World War I played a key role in shaping modern housing policy. While in the pre-War era, there was virtually no housing policy, hostilities led to an almost immediate and comprehensive state intervention in the housing market, particularly among those engaged in the war. Originally, Russia went the same way as the other countries. However, after the communists seized power in November 1917, they started conducting a different policy reflecting their specific objectives. These differences become apparent when Soviet Russia is compared with Germany—a large European market economy that faced similar challenges: the devastating consequences of World War I, hyperinflation in the early 1920s, and the dictatorship regime of the 1930s. Thus, the diverging characteristics of the housing policy of both countries can to a large extent be attributed to the ideological differences between the centrally planned and the market economies.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer bundesweiten Konsortiallizenz in der Nachfolge einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. – This publication is with permission of the rights owner freely accessible due to an consortial licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Germany; Russia; Housing policy; World War; Rationing; Tenant eviction; Rent control; Nationlization